The Use of Harmonic Training in Developing Some Motor Capabilities and Offensive Skills in Handball - Azeez Salman, Hardan (International Journal of Psychosocial Rehabilitation, 2020)
This section includes the introduction and research problem, represented by the obvious weakness found in handball players when performing the offensive skills. The researchers attributed this to the lack of harmony and sense of the ball among the players, resulting from the lack of concentration of many coaches on this aspect, which led researchers to address this problem in an attempt to resolve it through the use of harmonic training and knowing the extent of its effects on the development of some motor capabilities and offensive skills in handball of the second stage students in the Faculty of Physical Education and Sport Sciences. The objectives included identifying the effects of harmonic training in the development of some motor capabilities and skills and offensive skills of the experimental and control groups for students of the second stage handball. As well as the hypotheses of research, there are statistically significant differences between the pre- and post-tests of the experimental and control groups in some offensive handball skills and in favor of the post-test. The study sample consisted of 20 students of the Faculty of Physical Education and Sport Sciences, Al-Mustansiriyah University, where the researchers concluded: It was found that harmonic training has a significant effect on the development of some offensive handball skills in students of the second stage. The researchers recommended the need to use harmonic training in the main part of the educational module because of its positive and effective influence at the level of performance.